Structural reforms and income distribution - Causa, Orsetta (OECD Economic Policy Papers, 2015)
This paper provides new empirical evidence on the effects of structural policies on household disposable incomes at different income levels. More specifically, it investigates the extent to which structural policies have differential long-run impacts on GDP per capita and on household incomes at different points of the distribution. One aim is to verify whether policy decisions may face tradeoffs between objectives of economic efficiency and equity. Many growth enhancing structural reforms are found to deliver stronger income gains for households at the lower end of the distribution compared with the average household, an indication that they may reduce inequality in disposable incomes. Such is the case of reducing regulatory barriers to domestic competition as well as to trade and FDI; stepping-up job-search support and activation programmes. Conversely, other reforms involve trade-offs between the efficiency and equity objective. This is the case of the tightening of unemployment benefits for the long-term unemployed, which is found to lift GDP per capita and average household incomes, but also to reduce disposable incomes at the lower end of the distribution